Role of Digital Technologies in The Process of Future Teachers’ Professional Development - Irina Kuzina; Valentina Mironycheva (ARPHA Proceedings, 2020)
Digitalizing of Higher pedagogic education and consequent changes taking place in modern society are an important, but understudied, cause for concern. Active implementation of information and communication technologies in almost all spheres of life requires a new approach to the training of the 21st century teacher. This is a teacher who determines students' socialization and adaptation to independent life, meaning that such teacher has to meet all the challenges of the time.The purpose of the article is to determine the role of digital technologies in the process of future teacher's professional development and the impact on the effectiveness of pedagogical activity of a young specialist in the digital educational environment at school.The leading methods for determining the role of digital technologies in the process of professional development used in the study are the following: analysis of pedagogical activities, observations, questionnaires, survey and testing. Modern Russian educational space in the last few years is undergoing major changes associated with the development and active implementation of digital technologies in schools, with the transformation of experience in learning and education concerning the younger generation. The goal of Higher education is to train teachers of a new format, able to integrate traditional methods and innovations related to the digitalization of education. The results showed that digital technologies make it possible to achieve goals twice as fast and make teaching more productive. Also, students are more motivated to acquire knowledge.